gp130 cytokine signaling in the pituitary gland: A paradigm for cytokine-neuro-endocrine pathways - Arzt, E. (2001)
Specific receptors for the different gp130 cytokines, as well as the cytokines themselves, are expressed in anterior pituitary cells, providing the basis for the regulation of hormone secretion and cell growth (Figure 2). During an inflammatory response, both IL-6 and LIF increase (15, 17). LPS stimulates intrapituitary IL-6 production in FS cells via specific Toll receptors using the p38 MAPK-NF-κB pathway (20). Anti-IL-6 antibodies block the ACTH response of rat anterior pituitary cell cultures to LPS, showing the involvement of locally produced IL-6 (U. Renner et al., unpublished observations). Thus, during acute or chronic inflammation or infection, systemic, hypothalamic, or hypophyseal gp 130 cytokines may act on anterior pituitary cells, integrating the neuroendocrine response. The action of gp130 cytokines through the STAT3 transcription factor represents a powerful mechanism for regulation of pituitary corticotroph function. In response to different stressful stimuli, CRH stimulates the corticotrophs through cAMP/protein kinase A-mediated and calcium-mediated pathways and AP-1, CREB, and Nurr transcription factors. Cytokines may act on corticotrophs through different mechanisms; whereas IL-1 acts through Nur77, gp130 employs STAT3 for transcriptional activation. Cooperation between STAT3 and other transcription factors, such as NF-κB, AP-1, or the glucocorticoid receptor, has been described in other tissues (6), but it remains to be established whether this occurs in the pituitary. Future research clarifying the molecular mechanisms of gp130 action on pituitary cells will provide new clues regarding their involvement in neuro-endocrine responses to immune stimulation and will be of great importance for understanding pituitary pathophysiology.